Analysis of The Application of Video Learning Media on Students' Learning Interest at The Tenth Grade of SMA Negeri 1 Gunungsitoli in 2022/2023 - Risky Islamuddin; Yasminar Amaerita Telaumbanua; Adieli Laoli; Elwin Piarawan Zebua (Journal on Education, 2023)
In advancing education, an effort is needed in running it. One of them is by utilizing technological advances that have been very developed along with the passage of time so far. In addition to the utilization of technology, improvements are also needed in terms of educational tools used such as innovation in learning, and teacher creativity in teaching in the classroom. Video Learning Media is one of the learning media that is often used. Video can be used as a learning media that contains educational content that can help students learn. Based on observations, researchers found that students sometimes feel less interested in the material being taught and students are also less interested in understanding the contents of textbooks. The formulation of the problem in this study is how much interest do students have in video learning media in class X SMA Negeri 1 Gunungsitoli in 2022/2023? The method used in this research is qualitative analysis. The research data collection used field notes, questionnaires, and documentation. After analyzing the results of the research findings, it is concluded that the application of video learning media to students learning interest at SMA Negeri 1 Gunungsitoli made students interested. Animation, music, sound and clear discussion made students like video learning media, beside that, it was easy for students to better understand the visualized learning. Teachers can also use videos as their learning media, which of course attracts students' interest in the material presented and affect students learning outcomes.